The Effect of Basic Damage on Postpartum Mothers Before and After Giving Cabbage Leaf Compress at Clinic X - Wulan, Sri (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Damage to breast milk occurs due to narrowing of the lactiferous duct, which results in remaining breast milk being trapped in it and causing swelling in the breast. This swelling can be treated with various methods, including the use of drugs or non-pharmacological approaches. One non-pharmacological method is to use a cabbage leaf compress on nipples that are experiencing pain and swelling. This procedure is recommended to be done for 30 minutes and can be repeated for 2 to 3 days. Research was conducted to evaluate the effect of cabbage leaf compresses on breast milk dams before and after use. The research method used was a one group pretest posttest design, with 16 post partum mothers as the sample selected using accidental sampling technique at Clinic X. The measuring instrument used was an observation sheet, and the measurement results were analyzed using the t-test. The results of the study showed a significant change in the condition of breast milk dams before and after using cabbage leaf compresses, with a p-value of 0.015. Therefore, it is recommended for post partum mothers to use cabbage leaf compresses as a method to overcome breast milk dams in order to increase the smooth flow of breast milk.